Differential equations and applications : proceedings of the Third Scheveningen Conference on Differential Equations, the Netherlands, August 29-September 2, 1977 - Eckhaus, Wiktor; Jager, E. M. de (Eduardus Marie de) (North-Holland mathematics studies, 1978)
Proceedings of the Third Scheveningen Conference on Differential Equations, the Netherlands, August 29-September 2, 1977.